An updated checklist of the herpetofauna from Guerrero, Mexico - Palacios-Aguilar, Ricardo; Flores-Villela, Oscar (Zootaxa, 2018)
We present an updated checklist of the amphibians and reptiles for the state of Guerrero, Mexico. This list is based on bibliographic records, the revision of scientific collections and the authors’ field notes. The herpetofauna of the state includes 259 species (78 amphibians, 181 reptiles), of which three are introduced. The conservation status of all native species was assessed using three independent systems (NOM-059, IUCN and EVS). Finally, the geographic distribution of amphibians and reptiles is discussed in the context of both the biogeographic provinces within the state and the influence of road location on specimen collection patterns.